Modelagem de um banco de dados para a implantação de um SIG para suporte ao plano de desenvolvimento institucional da UFSCar. - Fonseca, Valéria Irlinda Pádua Sartini (2016)
The Campus of the Universidad Federal de Sao Carlos - UFSCar involves around eight thousand people in higher education and research. In the last years, the urbanized area of the Campus increased very fast. This great expansion generated a larger demand in planning, administration and controls of several facilities and services in the University. The information about the Campus is stored in different departments and the fast growth of its built area did with that the administrators need faster system to update those data. So, in this work it was developed a spatial database modeling for the implementation of a Geographical Information System - GIS to the UFSCar Campus. GIS is a tool able to store, to manipulate and to analyze data enabling periodic updating. The method used in this work was based on spatial database modeling. Three levels of modeling were applied. In the first level (Real World), it was made a research to evaluate the needs of information of the administrative sections and another research to evaluate the proposals of the Plano de Desenvolvimento Institucional (Plan for Institutional Development) - PDI, of UFSCar. In the second level (Conceptual), it was created a Diagram of Themes and a Partial Meta Model. In the third level (Representation), the spatial database model was created using the Geo-OMT's notation Model.